PENGAWASAN DISTRIBUSI PUPUK BERSUBSIDI DI KABUPATEN AGAM - Mulyani, Seri; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Fertilizers are a strategic means of production and play an important role in increasing productivity and production of agricultural commodities. The government provides fertilizer subsidies as an effort to protect and improve the ability of farmers to implement balanced fertilization, and improve food security. Presidential Regulation number 15 of 2011 stipulates subsidized fertilizers as goods under supervision. Supervision is carried out by Commission of Fertilizer and Pesticide (KP3) in Agam Regency which includes procurement and distribution, including type, amount, quality, marketing area and highest retail price, as well as procurement and distribution time (sixs right principle). However, in its implementation, the supervision carried out by KP3 Team in Agam Regency was still not optimal because there were still cases of fraud in the distribution of subsidized fertilizers. The purpose of this study was to determine the extent of the implementation of subsidized fertilizer supervision in Agam Regency. This research using the concept of theory supervision by Manullang (2015: 184), which is setting standards / measuring instruments, conducting assessments, and carrying out corrective actions. This study uses a purposive sampling technique with data collection techniques including: observation, interviews, and documentation. From the results of the study, we expected that KP3 can improve performance so that fraud does not occur again and fertilizers can be distributed to farmers with the sixs right principle.                                                                                                            Keyword: Supervision, Distribution, Subsidized Fertilizers